2014
DOI: 10.1504/ejim.2014.060770
|View full text |Cite
|
Sign up to set email alerts
|

The influence of academic staff's personal and professional characteristics on the decision to cooperate with industry

Abstract: University-industry cooperation is important for economic development, particularly at the regional level. Despite this relevance, there is still a lack of understanding regarding the underlying factors that drive the transfer of knowledge and technology. Therefore, this research aims to identify factors related to academic staff's personal and professional characteristics that influence the decision to cooperate with industry. To attain this objective, we built up a unique dataset of academic staff, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…FSO1 and FSO2 recall that the value of the win ubi award promoted by the HIE was the fundamental «launch pad» for the idea of forming the spinoff. In the same way, all the interviewees emphasize the symbiosis between the HEI and the business world, the former looking for contact with industry to apply and commercialize the results of research, taking advantage of learning processes resulting from different forms of interpreting information (Laukkanen, 2003;Metcalfe, 2006) and also (RSO) as an alternative due to the lack of public finance (Franco et al, 2014) and the business world as a source of knowledge, namely through highly qualified human resources (FSO1, FSO2, and FSO3 and DSO1, DSO2, and DSO3), contributing to the dynamics of economic innovation and growth (Gunasekara, 2006;Fromhold-Eisebith and Werker, 2013). The business culture in the HEI's local region greatly limits the HEI's power as a catalyst.…”
Section: Overcoming Barriers In Academicmentioning
confidence: 98%
See 1 more Smart Citation
“…FSO1 and FSO2 recall that the value of the win ubi award promoted by the HIE was the fundamental «launch pad» for the idea of forming the spinoff. In the same way, all the interviewees emphasize the symbiosis between the HEI and the business world, the former looking for contact with industry to apply and commercialize the results of research, taking advantage of learning processes resulting from different forms of interpreting information (Laukkanen, 2003;Metcalfe, 2006) and also (RSO) as an alternative due to the lack of public finance (Franco et al, 2014) and the business world as a source of knowledge, namely through highly qualified human resources (FSO1, FSO2, and FSO3 and DSO1, DSO2, and DSO3), contributing to the dynamics of economic innovation and growth (Gunasekara, 2006;Fromhold-Eisebith and Werker, 2013). The business culture in the HEI's local region greatly limits the HEI's power as a catalyst.…”
Section: Overcoming Barriers In Academicmentioning
confidence: 98%
“…Without financial resources, HEIs cannot continue their knowledge-generating activities, and therefore public policies have also tried to stimulate the creation of knowledge with a commercial value, as an alternative to public finance. This fact has changed the working behavior of researchers in recent years: to seek for research funding; to look for collaboration with industry given the lack of positions in HEIs and also due to the inherent prestige (Franco et al, 2014). Different university policies, such as the attitude toward surrogate entrepreneurs, preferred methods of technology transfer, equity investments, intellectual property protection, and the development model (e.g., proactive, planned, or spontaneous; Chiesa et al, 2000;Lockett et al, 2003), all of them play a role in contributing to or inhibiting academic spin-off activities (Rothaermel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics play a crucial role in predicting the variables related to academic research (Perkmann et al, 2013;Thune, 2009). Previous studies have reported critical individual characteristics of academics including gender (Boardman & Ponomariov, 2009;Franco, Haase, & Fernandes, 2014;Hale & Regev, 2014), age (Boardman & Ponomariov, 2009;Franco et al, 2014;Perkmann et al, 2013), previous experience (Giuliani, Morrison, Pietrobelli, & Rabellotti, 2010;Jackson & Michelson, 2015;Perkmann et al, 2013), scientific values (Boardman & Ponomariov, 2009;Salimi et al, 2015) and nationality (Boardman & Ponomariov, 2009;Salimi et al, 2015). Giuliani et al (2010) also highlighted the importance of researchers' demographic characteristics, such as gender and age, in describing the propensity of engaging in different types of UIC.…”
Section: Demographical Characteristicsmentioning
confidence: 99%
“…Other studies explore interactions between market and non-market actors (Doh & Lucea, 2013;Franco, Haase, & Fernandes, 2014), the impact of global value chains (GVCs) on economic and social upgrading processes (Omoteso & Yusuf, 2017), and the relationship between institutional characteristics and corruption (Lee, Oh, & Eden, 2010).…”
Section: Institutional Dynamics and Non-market Strategiesmentioning
confidence: 99%